THE INFLUENCE OF ETHICAL LEADERSHIP ON EMPLOYEE VOICE BEHAVIOR WITH PSYCHOLOGICAL SAFETY AND AFFECTIVE COMMITMENT AS MEDIATING VARIABLES: (A STUDY ON EMPLOYEES OF PT BIO FARMA (PERSERO)) - Feriaini Rachmawati Asmara; Neuneung Ratna Hayati (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to analyze the influence of Ethical Leadership on Employee Voice Behavior with Psychological Safety and Affective Commitment as mediating variables at PT Bio Farma (Persero), an SOE undergoing significant organizational transformation. This research drew on internal survey results indicating low employee satisfaction with leadership responsiveness and declining motivation and trust, underscoring the need for leadership practices that promote openness and psychological security. Method: A quantitative survey was used, collecting data from 323 permanent employees, proportionally sampled from a population of 1,671. All measurement items met validity standards (r > 0.361) and showed high reliability (Cronbach’s Alpha > 0.70). Classical assumption tests covering normality, multicollinearity, and heteroscedasticity confirmed that the data fulfilled the requirements for regression analysis.Result: The results show that Ethical Leadership has a positive and significant effect on Employee Voice Behavior both directly and indirectly. Psychological Safety mediates this relationship by increasing employees’ perceived safety in expressing ideas, while Affective Commitment mediates it through stronger emotional attachment and identification with the organization. These findings indicate that ethical, fair, and transparent leadership behaviors encourage constructive employee voice. The managerial implication is that PT Bio Farma (Persero) should strengthen ethical leadership competencies and build a psychologically safe and emotionally engaging work environment to enhance employee voice during organizational transformation. Keywords: Affective Commitment, Ethical Leadership, Psychological Safety Voice Behavior